Paragenesis Prospek Endapan Bijih Besi Daerah Tanjung Kecamatan Bontocani Kabupaten Bone, Sulawesi Selatan - Hasbi Bakri; Harwan Harwan; Alam Budiman Thamsi; Irzal Nur; Firdaus F; Andi Fahdli Heriansyah (Jurnal Geomine, 2021)
Iron ore is the second most abundant metal on earth. The characteristics of this iron ore usually consist of iron ore carrier minerals associated with other minerals. One area that has iron ore prospects is the Tanjung area, Bontocani District, Bone Regency. The purpose of this study was to determine the types of iron ore carrier minerals and their associations, mineralization characteristics and paragenesis of iron ore carrier minerals. The data collection technique is carried out directly in the field by taking random samples in the field according to field conditions. Laboratory analysis uses mineragraphic analysis to determine iron ore carrier minerals and their associated minerals and X-Ray Diffraction analysis to determine iron ore carrier minerals that are not identified by mineragraphic analysis. From the results of the study found iron ore carrier minerals magnetite, goethite and hematite and their associated minerals in the form of sulfide minerals in the form of pyrite, covelite and braunite. The iron ore textures found are replacement and intergrowth textures. Paragenesis of mineral deposits formed successively are magnetite, hematite, pyrite, cuprite, braunite and goethite.